A Case Study on Promoting Neuroplasticity in a Patient With Schizophrenia. Issue 2 (25th February 2015) - Puskar, Kathryn; Slivka, Cynthia; Lee, Heeyoung; Martin, Colin; Witt, Matthew
Abstract : Purpose: The purpose of this study is to introduce the concept of neuroplasticity, explore strategies that psychiatric nurse practitioners can use to improve cognitive functioning, and apply these strategies to a case study of a patient diagnosed with schizophrenia. Design and Methods: This study used an explanatory descriptive approach with a single‐case study to describe cognitive functioning in people with schizophrenia and to illustrate practical implications. Findings: Schizophrenia is a severe mental illness with typical onset in late adolescence and young adulthood. Cognitive impairment often accompanies schizophrenia and may lead to significant functional impairment. Research demonstrates that the brain is able to change (neuroplasticity) in response to environmental stimuli either negatively or positively. Evidence suggests intervention, including cognitive remediation, physical activity, and sleep, can positively modify neuroplasticity in schizophrenia and improve cognitive function, which may lead to improved quality of life. Practice Implications: Psychiatric mental health nurses need to offer cognitive enhancing strategies to take advantage of neuroplasticity. Ongoing nursing education regarding therapeutic neurocognitive approaches from basic research should be emphasized.